Juridical Analysis of Uncertified Land Sale and Purchase Ingrobogan District - Rio Marshel Sahertian; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2023)
This study, entitled Implementation of Sale and Purchase of Uncertified Land in Grobogan Regency, this study aims to determine the Implementation of Land Sale and Purchase in Indonesia According to the applicable Positive Law, and find out the legal consequences of the implementation of buying and selling land without certificates in Grobogan Regency and find out how the stages of buying and selling uncertified land can be carried out. This study aims to determine the implementation of land sale and purchase in Indonesia according to the applicable positive law, and to analyze and understand the legal consequences of the implementation of land sale and purchase without certificates in Grobogan Regency. The research method uses a sociological juridical approach. Research specifications using descriptive analysis, data sources used primary data and secondary data, primary data collection methods using conservation and interviews, secondary data collection methods using literature studies and document studies and data analysis methods using qualitative analysis methods. Based on the results of the study, it can be concluded that the sale and purchase of land according to positive law in Indonesia must be made by and before the authorized Land Deed Making Officer (PPAT) as evidenced by the Sale and Purchase Deed. Legal consequences of the implementation of the sale and purchase of land without a certificate in Grobogan Regency In buying and selling land without a certificate, it is very possible that there are legal consequences caused, namely the absence of transfer of land rights and uncertainty of the transfer of land rights, as well as the lack of guaranteed legal certainty and legal protection.